Pengorganisasian Chronic Care Model dalam Pengelolaan Keteraturan Kontrol Pasien Pasca Stroke RSUD Sultan Syarif Mohamad Alkadrie Kota Pontianak - Ade Muhammad Cahyadi; Lely Lusmilasari (Center for Health Policy and Management, 2017)
Background: Recurrent strokes are alarming because they can aggravate the situation and increase maintenance costs. With the prevalence of cases that continue to increase from year to year, the potential for lost follow-up in the regularity of post-stroke patient control. The organization of chronic care model-based services is able to maintain and bridge the regularity of post-stroke patient control whose service concept focuses on the patient's active participation and health system. This study aims to explore the organization of Chronic Care Model in the management of post-stroke patient control regularity. Methods: Qualitative research with case study design. Participants in this study is the administration consisting of elements of leadership and implementer that have met the criteria taken by way of purposive sampling time research February-April 2017 Research instruments in the form of interview guidelines, qualitative analysis. Results: Decision support refers to clinical practice guidelines, shared information through multiprofession coordination in education, service integration is still passive which has more emphasis on curative and rehabilitative. The design of the service system in the service policy on the implementation of using service standards and imposing a classless service, on the design elements of the lack of human resources health, as well as facilities and infrastructure, on the chronic service model refers to the structure and hierarchy of organizations that emphasize the responsibility of the service to the physician in charge of medical. Clinical information systems are not available for group support and information technology-based coordination to support high quality health services. Conclusion: Management of post-stroke patient control regularity can not be separated from the support and ability of the implementer as well. Service upgrades can be improved through the implementation of the Chronic Maintenance Model in which there are several important elements such as systematic configuration, updating in service system design, modern clinical information systems.